2021
DOI: 10.3390/ijms22094343
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Related Receptor Influences the Hemolymph Glucose Content by Regulating Midgut Trehalase Gene Expression in the Last Instar Larvae of Bombyx mori

Abstract: The expression of trehalase in the midgut of insects plays an important role in glucose supply to the hemolymph. Energy metabolism is usually regulated by the estrogen-related receptor (ERR). A decrease in ATP levels is caused by the ERR hindering glycolysis. However, the relationship between trehalose accumulation and ERR expression is still unclear. Here, we found that silkworm ERR (BmERR) is concentrated and BmERR expression is strongly correlated with trehalase in the midgut during the last instar silkworm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In addition, ERR was involved in carbohydrate metabolism, hypoxic metabolism and energy metabolism in Drosophila ( Tennessen et al, 2011 ; Li et al, 2013 ; Kovalenko et al, 2019 ). Our previous research also found that BmERR regulated the expression of glycolysis-related genes to participate in the development of silkworm embryos, and affected the glucose concentration in the midgut by regulating the expression of trehalase ( Long et al, 2020 ; Shen et al, 2021 ). These further implied that ERR might regulate 20E signaling by mediating nutritional metabolism, then affects insulin pathway and finally exerts its influence on 20E signaling.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, ERR was involved in carbohydrate metabolism, hypoxic metabolism and energy metabolism in Drosophila ( Tennessen et al, 2011 ; Li et al, 2013 ; Kovalenko et al, 2019 ). Our previous research also found that BmERR regulated the expression of glycolysis-related genes to participate in the development of silkworm embryos, and affected the glucose concentration in the midgut by regulating the expression of trehalase ( Long et al, 2020 ; Shen et al, 2021 ). These further implied that ERR might regulate 20E signaling by mediating nutritional metabolism, then affects insulin pathway and finally exerts its influence on 20E signaling.…”
Section: Discussionmentioning
confidence: 85%
“…Since the completion of the genome sequence, the silkworm ( Bombyx mori ) has become a widely used model insect for lepidopteran research, and a general model organism for life sciences, toxicology, and fungal infections ( International Silkworm Genome, 2008 ; Suetsugu et al, 2013 ; Meng et al, 2017 ; Abdelli et al, 2018 ; Nakajima et al, 2018 ; Matsumoto and Sekimizu, 2019 ). In previous research, we have demonstrated that the Bombyx mori ERR (BmERR) is involved in the growth and development of silkworm embryos and larvae by regulating the expression of glucose metabolism-related genes ( Long et al, 2020 ; Shen et al, 2021 ). and vitellogenin via the 20-hydroxyecdysone (20E) -EcR pathway in silkworm ( Shen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…DERR initiates the expression of pentose phosphate pathway (PPP)‐phosphogluconate dehydrogenase (PGD) in the fat body, a key enzyme in the PPP, which is essential for insect growth and energy storage (Beebe et al, 2020; Kovalenko et al, 2019). Bombyx mori ERR affects haemolymph glucose level (Shen et al, 2021). During the embryonic development of silkworm and Drosophila , ERR can directly regulate the expression of related genes in the glycolytic pathway, and the embryo uses glycogen provided by the mother for glycolysis (Long et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the larval stage, silk gland weight increases by increasing cell volume, becoming the heaviest organ, which will affect silk yield (Liang et al, 2018;Shen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The silk gland begins to become morphologically different at approximately 8 days after egg laying through the division of apical cells (Dhawan & Gopinathan, 2003). In the larval stage, silk gland weight increases by increasing cell volume, becoming the heaviest organ, which will affect silk yield (Liang et al, 2018; Shen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%